Approaches in the separation of mushroom metabolites - So, Regina (Animo Repository, 1996)
Isolation of polar metabolites is specially difficult where facilities are limited. Hence this study was conducted to come up with procedure applicable within the context of DLSU chemistry laboratory. To determine the most appropriate method of separation, the nature of the polar components was determined by qualitative analysis. Sugars were detected in the mushroom sample contained polar components (RID) Chloride ions were also detected in the same sample. Different approaches of separation were considered in this study. Separation of the highly polar components of crude mushroom extracts by HPLC on a reverse phase pre-packed column proved to be a good procedure. The best separation was attained using water:acetonitrile (9.5:0.5) at a flow rate of 0.5 and a UV wavelength of 240. The classical methods of separation are recommended as preliminary method of separation of mushroom metabolites. Semi-pure isolates were obtained using this method. A pure isolate from the terrestrial plant Artocarpus odoratossima was obtained using the classical methods of purification. The partial structure elucidation of the pure isolate was made through iH NMR, 13C NMR, and IR spectroscopy. The spectral data suggest an unsaturated, long chain poly-alcohol.